2019
DOI: 10.1002/ajhb.23351
|View full text |Cite
|
Sign up to set email alerts
|

Height and life satisfaction: Evidence from 27 nations

Abstract: Objectives: To evaluate the effect of height on life satisfaction. Methods:We use data from a recent multi-country survey that was conducted in 27 nations. Results: Our main finding is that height does have a strong positive effect on life satisfaction. These findings remain positive and significant when we use a comprehensive set of well-known covariates of life-satisfaction at both the individual and country levels. These findings also remain robust to alternative statistical specifications. Conclusions: Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Under similar conditions, the smaller the ASIS-GTD is, the more difficult it is to expose the femur, leading to a higher incidence of fracture [24]. Compared with Europeans and Americans, Chinese individuals are relatively short [25,26], which increases the difficulty of femoral exposure and the operation. Yang et al [27] reported increasing difficulty performing the operation with shorter femoral necks.…”
Section: Discussionmentioning
confidence: 99%
“…Under similar conditions, the smaller the ASIS-GTD is, the more difficult it is to expose the femur, leading to a higher incidence of fracture [24]. Compared with Europeans and Americans, Chinese individuals are relatively short [25,26], which increases the difficulty of femoral exposure and the operation. Yang et al [27] reported increasing difficulty performing the operation with shorter femoral necks.…”
Section: Discussionmentioning
confidence: 99%
“…With similar conditions, the smaller the ASIS-GTD, the more di cult the femur exposure, leading to a higher incidence of fractures [24]. Compared with Europeans and Americans, Chinese are relatively short [25][26], which made femoral exposure and operation more di cult. Shang Xifu et al [27] reported that the di culty of DAA surgery in patients with short femoral neck increased, and the quanti cation of femoral neck was complicated.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there is a large body of evidence which demonstrates that observable early‐life conditions have a powerful and hard‐to‐reverse impact on the stature of adults. Height captures very early investments in health and nutrition at the time when child was an embryo as well as in early childhood which are associated with a wide range of positive outcomes in the later life, for instance, educational attainments, occupational choice, status, and labor market income (Bargain & Zeidan, 2017; Case & Paxson, 2008a, 2008b, 2011; Case, Paxson, & Islam, 2009; Habibov, Luo, Auchynnikava, & Fan, 2019). Consequently, this study follows the above‐discussed tradition in economics and sociology by focusing on the influence of height on labor market outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, much less attention has been given to the influence of height on the greater likelihood of being employed although evidence that taller individuals are more likely to be hired as compared with shorter individuals can be found in peer‐reviewed and in gray literature (Rosenberg, 2009). In this regard, it is important to note that focusing on the relationships between height, earnings and occupational choices while ignoring the relationship between height and employment can be a mistake within the context of developing and post‐communist countries for three main reasons (Habibov, Luo, et al, 2019). First, even when someone who is employed earns a relatively low salary, they develop skills, experience and know‐how that they will later be able to use in higher‐paid positions later in their career.…”
Section: Introductionmentioning
confidence: 99%